2014
DOI: 10.1177/0363546514525910
|View full text |Cite
|
Sign up to set email alerts
|

Are Articular Cartilage Lesions and Meniscus Tears Predictive of IKDC, KOOS, and Marx Activity Level Outcomes After Anterior Cruciate Ligament Reconstruction?

Abstract: Background Identifying risk factors for inferior outcomes after ACL reconstruction (ACLR) is important for prognosis and future treatment. The goal of this study was to determine whether articular cartilage and meniscal variables are predictive of 3 validated sports outcome instruments after ACLR. Hypothesis/Purpose We hypothesized that articular cartilage lesions and meniscus tears/treatment would be predictors of the IKDC, KOOS (all 5 subscales), and Marx activity level at 6 years following ACLR. Study D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
247
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(275 citation statements)
references
References 46 publications
18
247
0
3
Order By: Relevance
“…Early symptoms predict postsurgical outcomes years after an ACL reconstruction. [24][25][26] Future longitudinal studies that assess whether baseline traumatic BML size can predict patient-reported outcomes years after surgery or that evaluate whether changes in traumatic BML size relate to changes in knee pain will help build on these findings. Second, it remains unclear if the associations presented here were confounded by inflammation or concurrent injuries (eg, meniscal injury or chondral lesions) that could have contributed to the development of both traumatic BML volumes and knee pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early symptoms predict postsurgical outcomes years after an ACL reconstruction. [24][25][26] Future longitudinal studies that assess whether baseline traumatic BML size can predict patient-reported outcomes years after surgery or that evaluate whether changes in traumatic BML size relate to changes in knee pain will help build on these findings. Second, it remains unclear if the associations presented here were confounded by inflammation or concurrent injuries (eg, meniscal injury or chondral lesions) that could have contributed to the development of both traumatic BML volumes and knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, preoperative knee and body pain are important predictors of postsurgical outcomes 1 or 2 years after an ACL reconstruction. 25,26 Thus, enhancing our understanding of the factors involved in posttraumatic pain may be important in improving long-term results for the ACL-injured population.…”
mentioning
confidence: 99%
“…Pietrosimone et al 4 observed larger correlations (r ¼ 0.78) and stronger predictability (R 2 ¼ 0.61) between strength and IKDC scores in patients who had undergone ACL-R. Their ACL-R cohort reported levels of disability (IKDC score ¼ 86.1 6 8.9) and postoperative time (4.5 6 3.4 years) similar to those in our study; yet their peak torque values (2.73 6 0.57 Nm) were higher and their sample size (n ¼ 15) was smaller. 4 Multiple variables may contribute to subjective knee function after ACL-R, including psychological factors, 31 surgical technique, 32 associated knee damage, 33 activity demands, 34 and overall health of the patient. 35 The results of our predictive model indicated that as months after surgery increased (ranging from 6 to 107 months [8.9 years]), subjective knee function increased.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that evaluate long-term subjective results have found that partial meniscectomy is associated with lower scores than seen in patients with intact menisci. 8,28 The mean time of subsequent MMT in our study group was 3.6 years after ACL reconstruction. Shelbourne and Gray 8 showed that patients who underwent meniscectomy did not begin to have a decline in subjective scores until around 10 years after surgery.…”
Section: Discussionmentioning
confidence: 91%